Numerical simulation of 3D turbulent isothermal flow in a vortex combustor - Ridluan, Artit; Eiamsa-ard, Smith; Promvonge, Pongjet (My University, 2007)
Numerical simulations of strongly swirling turbulent flows in a vortex combustor (VC) are conducted. A comprehensive investigation of a three-dimensional isothermal VC flow using three first-order turbulence models: the standard k-ε turbulence model, Renormalized Group (RNG) k-ε model and shear stress transport (SST) k-ω model; and a second-order turbulence model, Reynolds stress model (RSM) together with a second-order numerical differencing scheme is conducted in the present work. The computation indicates that the RSM is superior to the other turbulence models in capturing the swirl flow effect in comparison with measurements. The numerical results for the VC flow provide the characteristics of the flow in terms of relevant parameters for the VC design and operation, composed of axial and tangential velocities, pressure fields, and turbulence kinetic energy. © 2007 Elsevier Ltd. All rights reserved.
Keywords: Isothermal flow; Swirl flow; Turbulence modeling; Vortex combustor (VC)